Physiological Signal Processing for Individualized Anti-nociception Management During General Anesthesia: a Review - De jonckheere, J.; Bonhomme, V.; Jeanne, M.; Boselli, E.; Gruenewald, M.; Logier, R.; Richebé, P. (Yearbook of Medical Informatics, 2015)
Objective: The aim of this paper is to review existing technologies for the nociception / anti-nociception balance evaluation during surgery under general anesthesia.Methods: General anesthesia combines the use of analgesic, hypnotic and muscle-relaxant drugs in order to obtain a correct level of patient non-responsiveness during surgery. During the last decade, great efforts have been deployed in order to find adequate ways to measure how anesthetic drugs affect a patient’s response to surgical nociception. Nowadays, though some monitoring devices allow obtaining information about hypnosis and muscle relaxation, no gold standard exists for the nociception / anti-nociception balance evaluation. Articles from the PubMed literature search engine were reviewed. As this paper focused on surgery under general anesthesia, articles about nociception monitoring on conscious patients, in post-anesthesia care unit or in intensive care unit were not considered.Results: In this article, we present a review of existing technologies for the nociception / anti-nociception balance evaluation, which is based in all cases on the analysis of the autonomous nervous system activity. Presented systems, based on sensors and physiological signals processing algorithms, allow studying the patients’ reaction regarding anesthesia and surgery.Conclusion: Some technological solutions for nociception / antinociception balance monitoring were described. Though presented devices could constitute efficient solutions for individualized anti-nociception management during general anesthesia, this review of current literature emphasizes the fact that the choice to use one or the other mainly relies on the clinical context and the general purpose of the monitoring.
Keywords: Physiologic monitoring; general anesthesia; nociception; tranducers; digital signal processing